Evaluation of the Characteristics of Interpersonal Communication among Postgraduate Students from Different Nationalities at a Malaysian Public University - Sarwari, Abdul Qahar; Muhammad Nubli, Abdul Wahab; Nor Ashikin, Abdul Aziz (University Putra Malaysia (UPM), 2016)
Communication among students from different nationalities who stay and study in multicultural university campuses is an important issue for their personal and academic lives. Among other concepts of communication, interpersonal communication which requires the direct interactions among communicators is important to be assessed. This study was carried out to assess the characteristics of interpersonal communication among international postgraduate students of a Malaysian public university. This study had 128 participants from 17 different countries, and the quantitative and qualitative methods were applied for the data collection procedure. Based on the results from this study, their stay and study in a multicultural university campus with students from various backgrounds helped the participants to have opportunities to interact with different people, and to gain some new personal and social skills and information. The results from this study confirmed that most of the participants of this study who were from different countries had daily interactions with students from other nationalities, and were comfortable and satisfied when interacting with their international peers. Based on the results, personal skill building was among the main reasons that encouraged the participants to leave their own countries and enroll at a multicultural university abroad. The results from this study may encourage university students to have more interactions with their peers and may also help researchers to focus on the related issues in the future.